Localizable entanglement of isotropic antiferromagnetic spin-1/2 chain - (:unkn) unknown (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2019)
The bounds of entanglement on antiferromagnetic (AF) isotropic Heisenberg spin-1/2 chain including dipole-dipole interaction (D) were investigated. The Quantum Monte Carlo method based on loop algorithm was employed to calculate the two-spin and single-spin expectation values mediating the lower and upper bounds. It was revealed that D and B-z (the applied magnetic field) were pivotal parameters in controlling either entanglement creation/extinction or entanglement enhancement/weakening. Rival regions indicated a revival phenomenon depending on the temperature for various strengths of D which also showed a nonmonotonic behavior under certain B-z identifying critical points. Even if thermal agitations break the stability of strong D entanglement, it remains invariable at very low temperatures.
Keywords: Localizable entanglement; loop algorithm; Heisenberg model; dipole-dipole interaction